دراسة بنمط الدفعة الواحدة لإمتزاز صبغة المثيلين الأزرق من محلولها المائي باستخدام بقايا القهوة المستهلكة: لديهم صندوق بريدي - العزابي خالد ي.; أبودية جمال أ.; الفيتوري سالم ع.; بن علي صالح; الغنودي يونس ع. (The Libyan Journal of Science, 2018)
The field of leathers and textiles with diversity of colours is considered the biggest industries contributing to the production of huge amounts of waters polluted with dyes. Basic dyes are among many classes of dyes and coloring materials; methylene blue dye (MB) is one type of such class. The removal of dyes from industrial wastewater has represented an obsession which alarmed people to the environmental issues. Industrial wastewater polluted with dyes can impose risk to the environment and people`s health. In this study, investigations on the feasibility of using consumed coffee residue (CCR) in removal of MB from its aqueous solution were carried out. Batch kinetics mode adsorption and equilibrium isotherm experiments were studied for the investigation of the studied dye. The effect of some physical variables such as initial concentration of MB dye, mass of adsorbent, size of adsorbent, time of shaking on the adsorption process were analyzed. The final results showed that equilibrium data of the adsorption process fitted to the Pseudo second order kinetic model. The mass of the adsorbents (CCR) and their sizes can significantly have an effect on the adsorption process. Besides, a clear correlation was found between the increment of initial concentration of MB dye and its result on the increment of adsorption capacity (q). From the results, it was proved that the equilibrium data is also consistent with Langmuir Isotherm Model.